Morphology of the inferior laryngeal nerve (recurrent nerve) in the anterior cervical region: A report of 30 thyroidectomies - Mame Sanou Diouf; Moustapha Ndiaye; Jean Marc Ndiaga Ndoye; Magaye Gaye; Malick Ndiaye; Abdoulaye Ndiaye; Raymond Diouf (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2023)
Objective: To study the morphological peculiarities of the left and right Inferior Laryngeal Nerves (ILN) in the anterior cervical region and their variations induced by thyroid pathology. Materials and methods: The study concerned 30 patients who underwent thyroidectomy at the ENT and cervico-facial surgery department of Idrissa POUYE general hospital (HOGIP) from June 1st, 2018 to June 30, 2019. Age, sex, morphotype, operative indication, type of thyroidectomy, route, morphometry, and mode of termination of the ILN were studied. Results: The mean age was 42 years. There were 29 women and one man. Eleven patients (36.7%) were brevilinear, 8 patients (26.6%) were longilinear and 11 patients (36.7%) were of intermediate morphotype. Multinodular goiter was the indication for surgery in 18 cases. A total of 53 ILNs were studied (29 left and 24 right). Path variations concerned 8 left recurrent nerves (28%). The mean diameter of the ILN was 2mm. Longilinear patients and those with intermediate morphotypes had the longest recurrent nerves, while brevilinear patients had the thickest nerves. On the right, the ILN was bifid in 10 cases (41.6%), trifurcated in 3 cases (12.5%), and fan-shaped in 1 case (4.1%). On the left, it was bifid in 23 cases (79.3%) and trifurcated in 2 cases (6.8%).  Conclusion: The caliber of the recurrent nerve is relatively large, and can sometimes be spindly, especially on the right. Morphotype may predict ILN dimensions. Extra-laryngeal division of the ILN is a common situation.